Thematic Interpretation of the Obligation to Study and Its Influence on Students' Morals and Ethics - Hafid; Cecep Anwar; La Ode Nursyah Dendi; Mahadi Ihsanuddin Ramadhan (al-Afkar, Journal For Islamic Studies, 2026)
Moral education in Islam is a very important aspect of shaping the character of individuals and society. Islam is not merely a set of religious teachings but also a comprehensive system that governs human behavior and ethics. Islam emphasizes the importance of possessing good and noble character in every aspect of life. This research employs a qualitative research method. Based on the object and theme of the discussion, this study falls under the category of library research, which relies on data sources from related literature. Learning is defined as the process of constructing meaning or understanding from information and/or experience. In the field of education, ethics and morals play a crucial role in shaping individual character and behavior. Ethics and morals serve as the foundational principles in the teaching and learning process, as well as in forming the values applied within educational and societal environments.